2001
DOI: 10.1046/j.1471-4159.2001.00275.x
|View full text |Cite
|
Sign up to set email alerts
|

Control of serotonergic neurons in rat brain by dopaminergic receptors outside the dorsal raphe nucleus

Abstract: We studied the control of dorsal raphe (DR) serotonergic neurons by dopaminergic transmission in rat brain using microdialysis and single unit extracellular recordings. Apomorphine (0.5±3.0 mg/kg s.c.) and quinpirole (0.5 mg/kg s.c.) increased serotonin (5-HT) output in the DR and (only apomorphine) in striatum. These effects were antagonized by 0.3 mg/kg s.c. SCH 23390 (in DR and striatum) and 1 mg/kg s.c. raclopride (in DR). 5-HT 1A receptor blockade potentiated the 5-HT increase produced by apomorphine in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 61 publications
1
43
0
Order By: Relevance
“…As dopaminergic innervation of the hippocampus is low, no augmentation of DA levels were detectable. It has been previously shown that DA D 1 -specific compounds had no effect on the turnover of 5-HT (Lappalainen et al, 1991), and that the DA D 2 receptor agonist increased local 5-HT release in RN (Ferre S and Artigas F, 1993), although this effect may be mediated at D 2 receptors localized outside the raphe nuclei (Martin-Ruiz et al, 2001b). However, no effect was observed on extracellular DA levels in the raphe nuclei after a single administration, or the combination of the 5-HT 2C antagonist with citalopram, which renders an interaction with DA neurons less likely.…”
Section: Dopaminementioning
confidence: 97%
“…As dopaminergic innervation of the hippocampus is low, no augmentation of DA levels were detectable. It has been previously shown that DA D 1 -specific compounds had no effect on the turnover of 5-HT (Lappalainen et al, 1991), and that the DA D 2 receptor agonist increased local 5-HT release in RN (Ferre S and Artigas F, 1993), although this effect may be mediated at D 2 receptors localized outside the raphe nuclei (Martin-Ruiz et al, 2001b). However, no effect was observed on extracellular DA levels in the raphe nuclei after a single administration, or the combination of the 5-HT 2C antagonist with citalopram, which renders an interaction with DA neurons less likely.…”
Section: Dopaminementioning
confidence: 97%
“…On the other hand, the data suggest that D 2 dopamine receptors (but not D 1 ) within RLi/PAG seem to participate in the rewarding effects of heroin, since their blockade with eticlopride (a very selective D 2 antagonist; Seeman and Van Tol, 1994) reduced CPP to heroin in a dose-dependent manner. D 2 dopamine receptors are known to be expressed by PAG neurons (Bouthenet et al, 1987;Martin-Ruiz et al, 2001), but the presence and distribution of D 1 dopamine receptor in neurons of RLi/PAG has not been described so far. The present study indicates that a population of RLi/ PAG neurons expressing D 2 dopamine receptors are involved in the modulation of heroin's rewarding effects.…”
Section: Thmentioning
confidence: 99%
“…However, these receptors could be also heteroceptors located on nondopaminergic neurons, and D 2 -mediated effects could be indirect through a modification of other neurotransmitter systems such as the midbrain serotonergic one. Thus, it is known that dopamine depolarizes midbrain serotonin neurons by an action on DA D 2 receptors (Haj-Dahmane and Shen, 2000), and systemic quinpirole (D 2 agonist) enhances serotonin release in the DR (Martin-Ruiz et al, 2001), and it has been proposed that DA D 2 receptors outside the DR (likely on PAG GABA neurons) control serotonergic activity in this nucleus (Martin-Ruiz et al, 2001). Furthermore, DR serotonin neurotransmission is involved in CPP, because local infusions of the 5-HT 1 agonist 8-OH-DPAT into the DR produce CPP (Fletcher et al, 1993).…”
Section: Thmentioning
confidence: 99%
“…The interactions between various types and subtypes of GluR, second messenger molecules, eicosanoid metabolites, reactive oxygen species (ROS), reactive nitrogen species (RNS), lipid peroxidation products (LPP), and phosphorylating enzymes make control of these systems extremely complex. Studies of Martin-Ruiz et al [50] have disclosed that GluR also interact with serotonergic, adrenergic, and cholinergic neural nets as well.…”
Section: +mentioning
confidence: 99%